A New Approximate Method for Earthquake Behaviour of Worship Buildings - Pinar Usta; Özgür Bozdağ (Civil Engineering Journal, 2019)
Turkey is in seismically active region, so many earthquakes occur in this country in the last decades. Ancient worship buildings are vulnerable to seismic activity, as many historical buildings. So, it is important to understand that building’s behavior under seismic actions. In this paper, fifteen masonry worship building has been selected which are located and built-in different region in Antalya. The main reason for the paper is to assess the seismic vulnerability of worship building by using a new approximate method. The method which is proposed in this paper aims at a simple and fast procedure based on a simplified geometric approach for immediate screening of masonry buildings at risk.